Menstrual irregularities and related risk factors among adolescent girls - Varghese, Linda; Saji, Akhila; Bose, Parvathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Irregular menstrual cycle is a common issue faced by females in their reproductive age group. Problems associated with menstruation are really challenging faced by adolescent girls. Females face various problems associated with menstruation once they attain puberty. The main aim of the study was to identify menstrual irregularities and related risk factors among adolescent girls in selected district, Kerala. Methods: Descriptive survey design and total enumeration sampling technique was used for the study. The study was conducted in 356 adolescent girls between the age group of 17-22 years. Data was collected by using a semi-structured questionnaire. Results: The mean age of the adolescent girls was 20 years. Majority of them belong to middle-class family (97.2%) with normal BMI (68%). 84% (299) girls have regular menstrual cycle and 16% of the girls have irregular menstrual cycle. Only 24 (6.7%) of girls have amenorrhea. Considerable number of adolescent girls 51 (14.3%) had light menstrual flow. More than half (65%) of the adolescent girls had menorrhagia. Polymenorrhagiais experienced by 11 (3.1%) of adolescent girls. Dysmenorrhea was present in 264 (94%) girls followed by menometrorrhagia (16%) and oligomenorrhea (14.9%). Conclusions: Menstrual irregularities are very common in reproductive age group of females and the common menstrual irregularities found were dysmenorrhea, oligomenorrhea and menometrorrhagia. Hypomenorrhea and menometrorrhagia has significant association with age.